Induction of hepatic synthesis of serum amyloid A protein and actin. - Morrow, J F (1981)
Major changes in the mRNA population of murine liver occur after administration of bacterial lipopolysaccharide, an agent that causes increases in the concentrations of acute-phase serum proteins. The mRNA for one of these, serum amyloid A, is increased at least 500-fold compared to the normal level. It becomes one of the most abundant hepatic mRNAs, and serum amyloid A synthesis comprises about 2.5% of total hepatic protein synthesis in the acute-phase response. Its synthesis is tissue-specific in that amyloid A mRNA was not detected in the kidney, an important site of amyloid fibril accumulation. The protein synthesized in largest amount by acute-phase liver tissue in culture is cytoplasmic actin. Its relative rate of synthesis is increased about 5-fold compared to the normal tissue; that of serum albumin is decreased to about one-third of its normal rate. The concentration of mRNA for serum albumin is decreased by a similar amount. Starting with induced liver RNA, we have constructed a recombinant plasmid containing most of the DNA sequence encoding the serum amyloid A polypeptide.